Community Legal Awareness in the Implementation of Land Administration in Tanjung Bunga Village - Afdol Tasmara; Susi Fitria Dewi; Maria Montessori; Aldri Frinaldi (Universitas Kuningan, 2022)
This research is motivated by the low legal awareness of the community in the administration of land administration in Tanjung Bunga Village. This study aims to analyze the mechanism, the causes of the low legal awareness, and how to increase the legal awareness of the community in certifying land. This research is qualitative descriptive research with a case study method. In determining the informants, the researcher used a purposive sampling technique consisting of 27 people, and the data were obtained through observation, interviews, and documentation. All data were tested for validity using Source Triangulation. In the data analysis technique, the researcher uses data reduction (data reduction), data presentation (data display), and conclusion drawing (verification). The results showed that the mechanism used to certify land had three stages, consisting of land registration procedures, time for obtaining certificates, and costs for obtaining land certificates. The factors that cause low public awareness of land certification are based on 3 (three) factors, namely, community confidence, less than optimal socialization methods, and less availability of time from the community. The efforts that have been made are asking for help from the land office to provide socialization to the village community, taking advantage of the free land certificate program from the government, and visiting each resident's house by Tanjung Bunga Village officials. This study concludes that the government's efforts to certify community land still have serious challenges due to the belief factor owned by the community.